El teatro de Miguel de Cervantes - García Aguilar, Ignacio; Gómez Canseco, Luis María, 1963-; Sáez, Adrián J. (Biblioteca filológica hispana ;, 2016)
This book seeks to offer for the reader a clear and simple image of the plays of Cervantes, generally overlooked by critics, as well as the influence of Cervantes on genre and his comedic contemporaries.